AOIR ETHICS PANEL 2: PLATFORM CHALLENGES - Gliniecka, Martyna; Reagle, Joseph; Proferes, Nicholas; Fiesler, Casey; Gilbert, Sarah; Jones, Naiyan; Zimmer, Michael; Xia, Huichuan; Sehat, Connie Moon; Prabhakar, Tarunima; Kaminski, Aleksei (AoIR Selected Papers of Internet Research, 2021)
This panel is one of two sessions organized by the AoIR Ethics Working Committee. It collects five papers exploring a broad (but in many ways common) set of ethical dilemmas faced by researchers engaged with specific platforms such as Reddit, Amazon’s Mechanical Turk, and private messaging platforms. These include: a study of people's online conversations about health matters on Reddit in support of a proposed situated ethics framework for researchers working with publicly available data; an exploration into sourcing practices among Reddit researchers to determine if their sources could be unmasked and located in Reddit archives; a broader systematic review of over 700 research studies that used Reddit data to assess the kinds of analysis and methods researchers are engaging in as well as any ethical considerations that emerge when researching Reddit; a critical examination of the use of Amazon’s Mechanical Turk for academic research; and an investigation into current practices and ethical dilemmas faced when researching closed messaging applications and their users. Taken together, these papers illuminate emerging ethical dilemmas facing researchers when investigating novel platforms and user communities; challenges often not fully addressed–if even contemplated–in existing ethical guidelines. These papers are among those under consideration for publication in a special issue of the Journal of Information, Communication and Ethics in Society associated with the AoIR Ethics Working Committee and AoIR2021.